Thermodynamic analysis of an improved adiabatic compressed air energy storage system. (1st December 2016) - Peng, Hao; Yang, Yu; Li, Rui; Ling, Xiang
Highlights: Thermodynamic analysis is presented for an improved A-CAES combined with PBTES system. A mathematic model is developed, validated and used to simulate system performances. PBTES heights have significant influence on the PBTES's thermal behaviors and the system efficiencies. The maximum cycle efficiency of the improved A-CAES system is 56.74%. Abstract: Energy storage technology is a cutting-edge research in the field of new and renewable energy application. In this paper we introduce the concept of an energy storage based on adiabatic compressed air energy storage (A-CAES) combined with packed bed thermal energy storage (PBTES) system. First, the system thermodynamic performance of a typical single cycle is discussed and the effect of PBTES heights is analyzed. The results show that an overall efficiency in excess of 49% is achievable and the PBTES heights have significant influence on the thermal behavior of PBTES, as well as the overall efficiencies. Because there is still heat energy remaining in the packed bed until the discharge process is terminated, an improved A-CAES system with a heat recuperator is further proposed. It is found that this improved system shows a promotion of ∼5% compared with the first present A-CAES system. The cycle efficiency of the improved system increases with the increase of continuous cycles, and then reaches a stable value of 56.74% after around 25 cycles. The main conclusions drawn from this work will be helpful for future development of a high-efficiency A-CAES system combined with PBTES.